Design Elements for a Computerized Patient Record - Adelhard, K.; Hölzel, D.; Überla, K. (Methods of Information in Medicine, 1999)
Computerized medical record systems have to present user-and problem-oriented views of a patient record to health-care professionals. Presentation and manipulation of data must be easily adaptable to current and future demands of medical specialties and specific settings. During the definition, development and evaluation of a prototype of a computerized patient record system, design elements were elaborated to support physicians and other health-care professionals. Our approach shows a high degree of flexibility and adaptability to specific needs, problem orientation and connectivity to other systems, via a hospital information network. The explicit description of the contents of a patient record allows to augment the number of items that can be recorded without modifying the data structure. New views on patient data can be added to the system without interfering with the routine use of the system. Application in several medical specialties proved the feasibility of our prototype.
Keywords: Computerized Medical Records; Problem-Oriented-Record; Hospital Information System; Data Model